Activation of GABAB receptors potentiates inward rectifying potassium currents in satellite glial cells from rat trigeminal ganglia: In vivo patch-clamp analysis. (12th March 2015) - Takeda, M.; Nasu, M.; Kanazawa, T.; Shimazu, Y.
Highlights: Immunoreactivity for Kir4.1 and the GABAB receptor was co-expressed in SGCs from the TRGs. Baclofen-induced potentiation of the Kir current was abolished by co-application of saclofen. Baclofen resulted in hyperpolarization of the membrane potential of SGCs. Activation of GABAB receptors in SGCs potentiates Kir currents in the absence of inflammation. GABA contributes to glial potassium homeostasis via SGCs GABAB receptor activation. Abstract: In a previous study, we demonstrated that inflammation suppressed inward rectifying K + (Kir) currents in satellite glial cells (SGCs) from the trigeminal ganglia (TRGs) and that this impairment of glial potassium homeostasis in the trigeminal ganglion (TRG) contributed to trigeminal pain. The aim of the present study was to investigate whether activation of GABAB receptors modulates the Kir current in SGCs using in vivo patch-clamp and immunohistochemical techniques. Immunohistochemically, we found that immunoreactivity for glial-specific Kir channel subunit Kir4.1 and the GABAB receptor was co-expressed in SGCs from the TRGs. In vivo whole-cell recordings were made using SGCs from the TRGs of urethane-anesthetized rats. Application of baclofen, a GABAB receptor agonist, significantly increased the mean peak amplitude of Kir currents in a concentration-dependent and reversible manner. Baclofen-induced potentiation of the Kir current was abolished by co-application of 3-amino-2-(4-chlorophenyl)-2-hydroxyprophylsulfonic acid (saclofen). In addition, baclofen significantly potentiated the density of the Ba 2+ -sensitive Kir current, and resulted in hyperpolarization of the mean membrane potential. These results suggest that activation of GABAB receptors potentiates the Kir current in SGCs and that GABA released from the TRG neuronal soma could contribute to buffering of extracellular K + concentrations following excitation of TRG neurons during the processing of sensory information, including the transmission of noxious stimuli.